2010
DOI: 10.3109/09513590.2010.507292
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the pathophysiology of endometriosis: from chronic inflammation to danger signal

Abstract: In conclusion, a circulus vitiosus of both the oxidative stress pathway and the TLR pathways is generated when the process becomes chronic (danger signal spiral).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 71 publications
1
74
0
1
Order By: Relevance
“…The diagnostic accuracy of each marker alone was either similar or worse than that of CA-125. The concentrations of various cytokines, growth and angiogenic factors, metalloproteinases, peptides, subpopulations of leukocytes and expression of various genes were examined in endo metriosis [17][18][19]. Nowadays researchers are trying to develop a statistical model based on three or four serum biomarkers which could have enough statistical power to diagnose endometriosis without the necessity of laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic accuracy of each marker alone was either similar or worse than that of CA-125. The concentrations of various cytokines, growth and angiogenic factors, metalloproteinases, peptides, subpopulations of leukocytes and expression of various genes were examined in endo metriosis [17][18][19]. Nowadays researchers are trying to develop a statistical model based on three or four serum biomarkers which could have enough statistical power to diagnose endometriosis without the necessity of laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…PAR is expressed in uterine endometrial stromal cells (23,24) and PAR activation has been shown to stimulate the production of matrix metalloproteinase (MMP)-1/2, VEGF, and IL-8 (41). One of the potential contributing factors in the progression of endometriosis is neutrophil elastase, which has been implicated in the inflammatory response in endometriotic tissues (42) and can activate PAR1/2 (21). Thus, bleeding may cause PAR1/2 activation through elastase activation.…”
Section: Discussionmentioning
confidence: 99%
“…TLR-mediated inflammation possibly occurs through the exogenous PAMPs as well as the endogenous danger-associated molecular pattern (DAMP) ligands (2). Nucleotide oligomerization domain-like receptors (NLRs) and, to a lesser degree, the retinoic acid-inducible gene I-like receptors are intracellular sensors (16).…”
Section: Role Of Initial Infectionmentioning
confidence: 99%
“…In addition to their response to various exogenous PAMPs, TLRs recognize a wide range of endogenous DAMPs, including high-mobility group box protein 1 (HMGB1), heat shock protein 70 (HSP70), adenosine-5'-triphosphate (ATP), DNA, urate crystals, asbestos, silica, aluminum hydroxide, S100, neutrophil elastase, amyloid-β and soluble extracellular matrix components, such as biglycan, hyaluronan, versican, fibrinogen, heparan sulfate fragments and fibronectin extra domain A (2,26,27). Intracellular contents released from damaged cells into the extracellular space serve as DAMPs or alarmins that trigger inflammation (Fig.…”
Section: Dampsmentioning
confidence: 99%
See 1 more Smart Citation